Mcp1p tracks microtubule plus ends to destabilize microtubules at cell tips. Issue 6 (11th February 2014) - Zheng, Fan; Li, Tianpeng; Cheung, Martin; Syrovatkina, Viktoriya; Fu, Chuanhai
Abstract : Microtubule plus ends are dynamically regulated by a wide variety of proteins for performing diverse cellular functions. Here, we show that the fission yeast Schizosaccharomyces pombe uncharacterized protein mcp1p is a microtubule plus‐end tracking protein which depends on the kinesin‐8 klp6p for transporting along microtubules towards microtubule plus ends. In the absence of mcp1p, microtubule catastrophe and rescue frequencies decrease, leading to an increased dwell time of microtubule plus ends at cell tips. Thus, these findings suggest that mcp1p may synergize with klp6p at microtubule plus‐ends to destabilize microtubules. Abstract : Mcp1p is a novel microtubule plus‐tip protein tracking both growing and shortening microtubules. Mcp1p is required for microtubule destabilization at cell tips. The kinesin‐8 klp6p transports mcp1p to microtubule plus ends.